Penilaian Kesejahteraan Petani Padi Menggunakan Indikator Pendapatan, Pangsa Pengeluaran Pangan dan Good Service Ratio di Kabupaten Lima Puluh Kota - Tiara Monica; Vicka Pramudya Putra; Veronice Veronice (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This research evaluates the degree of welfare among rice farmers in Harau and Luak Districts, Lima Puluh Kota Regency. This research examines household income levels and consumption expenditures from December 2024 to February 2025. A quantitative and descriptive approach is employed to conduct the study. Data were collected from 75 rice farmer respondents who were selected by purposive sampling and active rice farming. Primary data on income and expenditure were obtained through direct interviews, while the level of welfare was measured using a structured questionnaire. Two leading indicators were used to assess the farmer household welfare threshold: the share of food expenditure (PPP) and the good service ratio (GSR). PPP helps determine the portion of income spent on food, which indicates food security status, while RJN assesses The capacity of the household to fulfill essential non-food requirements, including education, healthcare, and housing. The study's findings indicate that the majority of rice farmers are vulnerable to food security because most of the population uses most of their income for food needs. This indicates limited financial ability to meet non-food needs. The GSR results also show that most farmers are classified as less prosperous, especially in the Luak District, which shows that rice farming alone is not enough to achieve a decent standard of living. Several factors that influence the welfare of rice farmers include education level, health and nutritional status, number of dependents, land area, labor participation, and residential environmental conditions. In addition, farmers' ability to balance food and non-food needs is an important determinant of their welfare.